The Relationship between Watching Television and Academic Achievement in 9th Graders Students - Kakamad, Karwan Kakabra; Fatah, Abdulfatah Hasan (Information Management and Business Review, 2018)
This study examines the relationship between watching television and academic achievement of school going 9th-grade students in Kurdistan region of Iraq. After a brief review of some related research and programs the ground realities and problems prevails in Kurdistan region of Iraq society regarding students spending time watching television, their life will be shaped by television, and this affects their academic achievements. The researcher used a quantitative Causal-Comparative research methodology, and 240 9th graders students selected in three different schools. Non-random purposive sampling was used to collect the data. in general, this study finds that television viewing has a moderately negative effect on the academic achievement. This means the more students spent time watching Television the less grade they will achieve in their school. Finally, there are some recommendations provided that should be taken by families and educators including, watching certain programs, co-viewing, having only one television at home.